Granny - Horowitz, Anthony (London Walker books Ltd, 2004)
Twelve-year-old Joe Warden isn't happy. Sure, he's rich, but his parents don't care about him. His grandmother should make everything better, except that Joe's granny is a nightmare. She's not just physically repulsive, she's horribly mean. Everyone thinks she's just a dotty old woman, but Joe knows the truth. He's seen behind her mask and glimpsed the wicked glimmer in her eyes - she is pure evil. And now she's out to get Joe, unless he can stop her and her band of nasty grannies first
Keywords: English fiction